The Concept of Ta'awun and Sharia Mutual Cooperation in Prosperity and the Establishment of Darus Salam Mosque - M Muthoifin; Muhammad Badat Alauddin; Meguellati Achour; Muhammad Ammar Al-amudi; Prabu Arya Sembara; Rozi Irfan Rosyadi; Ahmadi Abd Adzim; Rania Mahmoud ELSakhawy; Adnanda Yudha Rhezaldi; Muhammad Iqbal (Walidem Institute and Publishing (WIP), 2023)
In the view of sharia, prospering and building mosques is a sacred commandment and includes noble practices, as well as ta'awun and mutual aid are true forms of implementation of sharia. Therefore, the problem faced by partners is that the condition of the mosque is small and made of wood, worthy of renovation and the community is given guidance to be aware of the importance of ta'awun and prosper the mosque. So this construction took a big theme, namely how to build the community with the guidance of the concept of ta'awun and mutual aid syariah in prosperity and the establishment of a new Darus Salam mosque in Griya Salam Boyolali. The method used in this study is qualitative, a type of field study, with phenomenological, descriptive, and normative approaches to religion. The results of this guidance show that the concept of ta'awaun, cooperation, and mutual help, is a practical and effective concept for realizing socio-religious programs, especially in the construction of the Darus Salam Mosque in Griya Salam housing.